Thaumarchaeotes abundant in refinery nitrifying sludges express amoA but are not obligate autotrophic ammonia oxidizers - Mussmann, Marc; Brito, Ivana; Pitcher, Angela; Sinninghe Damsté, Jaap S; Hatzenpichler, Roland; Richter, Andreas; Nielsen, Jeppe L; Nielsen, Per Halkjær; Müller, Anneliese; Daims, Holger; Wagner, Michael; Head, Ian M (Proceedings of the National Academy of Sciences - PNAS, 2011)
Nitrification is a core process in the global nitrogen cycle that is essential for the functioning of many ecosystems. The discovery of autotrophic ammonia-oxidizing archaea (AOA) within the phylum Thaumarchaeota has changed our perception of the microbiology of nitrification, in particular since their numerical dominance over ammonia-oxidizing bacteria (AOB) in many environments has been revealed. These and other data have led to a widely held assumption that all amoA-encoding members of the Thaumarchaeota (AEA) are autotrophic nitrifiers. In this study, 52 municipal and industrial wastewater treatment plants were screened for the presence of AEA and AOB. Thaumarchaeota carrying amoA were detected in high abundance only in four industrial plants. In one plant, thaumarchaeotes closely related to soil group I.1b outnumbered AOB up to 10,000-fold, and their numbers, which can only be explained by active growth in this continuous culture system, were two to three orders of magnitude higher than could be sustained by autotrophic ammonia oxidation. Consistently, (14)CO(2) fixation could only be detected in AOB but not in AEA in actively nitrifying sludge from this plant via FISH combined with microautoradiography. Furthermore, in situ transcription of archaeal amoA, and very weak in situ labeling of crenarchaeol after addition of (13)CO(2), was independent of the addition of ammonium. These data demonstrate that some amoA-carrying group I.1b Thaumarchaeota are not obligate chemolithoautotrophs.